Augmented reality and virtual reality in our daily life - Vallidevi Krishnamurth; Nagarajan K. K.; D.Venkata Vara Prasad; Ganesh Kumar; Arjith Natarajan; Shailesh Saravanan; Akshaya Natarajan; Shankaran Murugan; Dattuluri Rushitaa (Institute of Advanced Engineering and Science, 2020)
Augmented reality, the new age technology, has widespread applications in every field imaginable. This technology has proven to be an inflection point in numerous verticals, improving lives and improving performance. In this paper, we explore the various possible applications of Augmented Reality (AR) in the field of Medicine. The objective of using AR in medicine or generally in any field is the fact that, AR helps in motivating the user, making sessions interactive and assist in faster learning. In this paper, we discuss about the applicability of AR in the field of medical diagnosis. Augmented reality technology reinforces remote collaboration, allowing doctors to diagnose patients from a different locality. Additionally, we believe that a much more pronounced effect can be achieved by bringing together the cutting edge technology of AR and the lifesaving field of Medical sciences. AR is a mechanism that could be applied in the learning process too. Similarly, virtual reality could be used in the field where more of practical experience is needed such as driving, sports, neonatal care training.